Investigation on some Soil Parameters for three Different Habitats of Mediterranean Region, Turkey - EVEREST, AYSE; ARSLAN, HAKAN (Asian Journal of Chemistry, 2010)
Some soil parameters (humidity, pH, conductivity, organic matters, total nitrogen, saturation percentage, field capacity, cation exchange capacity, exchangeable cations, available phosphorus and soil texture) in three different types of habitats and three different parts in the Mediterranean region in Turkey were investigated. Overall results revealed that the differences among measurements of the some soil parameters for the three types of habitats of the high plateaus were negligible. The results of soil parameters analysis indicate that the eroded habitats may be subject to rehabilitation.